Proptosis as a presenting sign of extradural haematoma. Issue 3 (March 1993) - Stewart, C R; Salmon, J F; Domingo, Z; Murray, A D
Abstract : A conscious 15-year-old boy presented with progressive proptosis and a severe headache 2 weeks after minor blunt trauma to the head. No neurological deficit was present. Computed tomography demonstrated intracranial and intraorbital cyst-like masses. At craniotomy a subacute extradural haematoma was found which communicated with an orbital subperiosteal haematoma through a shelved orbital roof fracture. The haematomas were drained and the patient made an uneventful postoperative recovery. Although rare, an extradural haemorrhage should be considered in any patient presenting to an ophthalmologist with progressive proptosis and headache following a head injury.